2005
DOI: 10.1038/sj.bjc.6602599
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a fragment of e-cadherin as a serum biomarker with predictive value for prostate cancer

Abstract: In prostate cancer, biomarkers may provide additional value above standard clinical and pathology parameters to predict outcome after specific therapy. The purpose of this study is to evaluate an 80 kDa fragment of the cell adhesion molecule e-cadherin as a serum biomarker. A broad spectrum of prostate cancer serum samples, representing different stages of prostate cancer disease, including benign prostatic hyperplasia (BPH), localised (Loc PCA) and metastatic prostate cancer (Met PCA), was examined for the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 33 publications
5
34
0
Order By: Relevance
“…sE-cad levels found in preoperative serum samples are in the range reported in the literature in patients affected by this or other types of cancers (5,13,15,16,28). Values determined in patients were significantly higher than those observed in healthy subjects according to reports by other authors (5,15,16,18,28).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…sE-cad levels found in preoperative serum samples are in the range reported in the literature in patients affected by this or other types of cancers (5,13,15,16,28). Values determined in patients were significantly higher than those observed in healthy subjects according to reports by other authors (5,15,16,18,28).…”
Section: Discussionsupporting
confidence: 61%
“…It has been reported that sE-cad is involved in stimulation of invasion in a paracrine manner, in promotion of cell junction disruption and of cell dissemination thereby inducing the migratory phenotype (19). Moreover, the highest expression levels of sE-cad have been found in patients with metastatic cancers, and high levels at the time of diagnosis are associated with a significant risk of biochemical failure (16)(17)(18) (17). Regarding interleukins (IL), they are pleiotropic cytokines with a wide range of biological activities including immune regulation, hematopoiesis, inflammation and oncogenesis (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…122 E-cadherin, b-catenin and matrix metalloproteinases are also involved in altered cell adhesion and cellular migration and appear to be promising biological markers associated with disease aggressiveness. 123,124 Other potential protein biomarkers include inhibitors of metalloproteinases, 125 hepatocyte growth factor, 126 macrophage migration inhibitory factor, 127 progastrin-releasing peptide 128 and 50.8 kDa protein. 129 Additional growth factors, including insulin-like growth factor (IGF)-I, IGF-II and IGF-binding protein-3 (BP-3) have been implicated in the etiology of both benign and malignant disease.…”
Section: Other Markersmentioning
confidence: 99%
“…Decreased E-cadherin expression is considered to be a central event in the disruption of the normal cell-cell adhesion required for the acquisition of the invasive and metastatic phenotype of various epithelial neoplasms, including PC [Bussemakers et al, 1992;Paul et al, 1997]. Aberrant E-cadherin expression was associated with a larger tumor size [Rubin et al, 2001], a higher tumor grade and stage, and an increased risk of disease recurrence after prostatectomy [Kuefer et al, 2005].…”
mentioning
confidence: 99%